Effect of 36 Years of Continuous Cropping and Fertilization on Productivity, Micro and Secondary Nutrient Status and Uptake by Maize-wheat Cropping System in Western Himalayas - Shambhavi, Shweta; Kumar, Rakesh; Sharma, S. P.; Verma, Gayatri; Sharma, Sanjay K.; Sharma, R. P. (International Journal of Bio-resource and Stress Management, 2018)
A study was conducted during 2008-09 to assess the changes in the soil status of secondary and micronutrients and micronutrients uptake by maize-wheat cropping system after 36 years of fertilizer use at CSKHPKV, Palampur, Himachal Pradesh, India. The exchangeable Ca and Mg and available S varied from 1.47-6.63, 0.17-0.52 c mol (p+) kg-1, 11.6-26.0 kg ha-1, respectively. An overall decline in exchangeable Ca and Mg status was observed as compared to its initial value in all the treatments over the years except in lime treatment where a build-up in Ca content was noticed. The available S status increased in all the treatments except control and 100% N as compared to its initial value. DTPA-extractable micronutrients in general showed a decline from its initial level except for Cu where a noticeable build-up has been observed. All the DTPA-extractable micronutrients were higher in FYM treated plots except DTPA-Zn being highest in 100% NPK+Zn treatment. The highest grain and stover/straw yields of maize and wheat were obtained in 100% NPK+FYM treatment (13.9 and 9.7 t ha-1, respectively) followed by 100% NPK+lime (mention yield 13.24 and 8.82 t ha-1, respectively), both being at par. Total uptake of Fe, Mn, Zn and Cu ranged from 62.9-2223.1, 17.4-986.6, 11.5-701.5 and 20.1-715.8 g ha-1, respectively by maize and from 197.4-1473.2, 112.2 -956.1, 44.1-395.0 and 69.4-586.0 g ha-1, respectively by wheat under different treatments.